Uang dan Keterasingan - Nelman Asrianus Weny (Indonesian Journal of Theology, 2018)
Money is, in of itself, an anonymous and neutral force. However, throughgoing capitalization in all dimensions of life has brought humankind to regard the making of money as its sole objective to be achieved by any means necessary. At the same time, the misuse of money breeds alienation. The expression, “Whosoever has the money, has the power,” only exacerbates alienation. As a social reality, alienation presents a confessional challenge to the church, including churches in Indonesia. Adopting an interdisciplinary approach, with particular emphasis upon philosophical and theological studies, I argue that the church bears ethical-moral responsibility for overcoming this challenge. The solution that I offer amounts to a “new language” for money within the framework of a “theology of money”: To meet its ministry obligations, the church needs money, yet the church must also combat the idolization of it. To wit, churches must dare to prove that each, whether as individual or institution, is truly free from all forms of monetary idolatry.